2014
DOI: 10.1310/tsr2102-137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neurofeedback and Electromyographic-Biofeedback Therapy on Improving Hand Function in Stroke Patients

Abstract: Patients in the neurofeedback and EMG-biofeedback groups showed hand improvement similar to conventional OT. Further studies are suggested to assign the best protocol for neurofeedback and EMG-biofeedback therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 22 publications
1
73
0
3
Order By: Relevance
“…An improved speech and motor function were also reported by above stroke patients. Similar findings of neurological recovery were recently described by Rayegani et al [1], where patients in the neurofeedback and EMG-biofeedback groups showed hand function improvement similar to conventional occupational therapy. The most likely explanation of positive role of NFB in CVA patients may be attributed to its neuroplastic effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An improved speech and motor function were also reported by above stroke patients. Similar findings of neurological recovery were recently described by Rayegani et al [1], where patients in the neurofeedback and EMG-biofeedback groups showed hand function improvement similar to conventional occupational therapy. The most likely explanation of positive role of NFB in CVA patients may be attributed to its neuroplastic effect.…”
Section: Discussionsupporting
confidence: 89%
“…EEG biofeedback also called neurofeedback (NFB) has been shown to be a promising modality in neurorehabilitation including stroke [1][2][3][4]. Recent progress in computer technology and development of newer imaging and NFB techniques including low resolution electromagnetic tomography analysis (LORETA) as well as Z-score NFB prompted me to apply this therapy in stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…The first, Rayegani et al. ( N  = 20)52 reported significant improvement in Jebsen Hand Function Test53 score in six out of seven test items in the neurofeedback group and only three in the occupational therapy group. The second, Jang et al 54.…”
Section: Resultsmentioning
confidence: 96%
“…A few single-blind experiments comparing neurofeedback to control treatments such as electromyography (EMG) biofeedback [27,28] and sham EEG-nf [29,30] demonstrated greater improvements in both healthy and patient populations in the veritable EEG-nf group. In contrast, recent studies showed that EEG-nf and EMG biofeedback were comparable for chronic pain [31], stroke rehabilitation [32], and ADHD [33]. Additional studies concerning pediatric ADHD have used stimulant medication as an active control while attempting to maximize expectancy in both groups by allowing the parents of the affected children to select between medication and neurofeedback [34][35][36].…”
mentioning
confidence: 99%